2011
DOI: 10.1021/jm200249a
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and SAR of Methylated Tetrahydropyranyl Derivatives as Inhibitors of Isoprenylcysteine Carboxyl Methyltransferase (ICMT)

Abstract: A series of tetrahydropyranyl (THP) derivatives has been developed as potent inhibitors of isoprenylcysteine carboxyl methyltransferase (ICMT) for use as anticancer agents. Structural modification of the submicromolar hit compound 3 led to the potent 3-methoxy substituted analogue 27. Further SAR development around the THP ring resulted in an additional 10-fold increase in potency, exemplified by analogue 75 with an IC(50) of 1.3 nM. Active and potent compounds demonstrated a dose-dependent increase in Ras cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 30 publications
1
27
0
2
Order By: Relevance
“…Thus, strategies that effectively curtail CaaX processing are still considered among the most viable approaches to anti-RAS therapeutics. Accordingly, ICMT is considered a good drug target, and enthusiasm for this approach has been bolstered by several preclinical studies that have found a requirement for ICMT in KRAS-mediated cellular transformation (9) and oncogenesis in vivo (10) as well as in studies suggesting that pharmacologic inhibition of ICMT blocks RAS-dependent transformation (44,45). We set out to solidify this view by studying the role of ICMT in a mouse model of PDA that more faithfully recapitulates human pathology than the cancer models previously examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, strategies that effectively curtail CaaX processing are still considered among the most viable approaches to anti-RAS therapeutics. Accordingly, ICMT is considered a good drug target, and enthusiasm for this approach has been bolstered by several preclinical studies that have found a requirement for ICMT in KRAS-mediated cellular transformation (9) and oncogenesis in vivo (10) as well as in studies suggesting that pharmacologic inhibition of ICMT blocks RAS-dependent transformation (44,45). We set out to solidify this view by studying the role of ICMT in a mouse model of PDA that more faithfully recapitulates human pathology than the cancer models previously examined.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that our results implicate for the first time the Notch pathway as one that must be considered when attempting to predict the pleiotropic effects of ICMT inhibition. Given the fact that in some models, ICMT deficiency ameliorates tumors (10) and that ICMT inhibitors have been shown to have antitumor activity (44,45), does our surprising observation that ICMT deficiency exacerbates KRAS-driven PanINs in one mouse model mean that ICMT inhibitors cannot be developed as drugs? This will depend on how generalized the results are that we report here.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even if they can be developed, RCE1 inhibitors may be more toxic overall than ICMT inhibitors. Nevertheless, attempts have been made to develop inhibitors of both RCE1 (39) and ICMT (40-42), although each will necessarily also affect alternate substrates in addition to RAS. Disappointingly, even the most potent and selective of the RCE1 inhibitors have recently been shown to lack mechanism-based activity (43).…”
Section: Targeting Post-prenylation Caax Processing: Rce1 and Icmtmentioning
confidence: 99%
“…A recent report that knocking out ICMT in a mouse model of pancreatic cancer exacerbated the disease (15) underscores the need for further studies exploring the potential utility of ICMT inhibitors. To date, only a few inhibitors of ICMT have been identified, and no clinical trials using these inhibitors have been conducted (13,16,17). The development of effective ICMT inhibitors will benefit from a detailed understanding of the active site of the enzyme.…”
mentioning
confidence: 99%